Nghiên cứu ảnh hưởng của tỷ phần pha tạp Co(II) lên kích thước và từ tính của vật liệu nano YFe1-xCoxO3 tổng hợp bằng phương pháp đồng kết tủa - Tiến, Nguyễn Anh; Diễm, Châu Hồng (Vietnam Journal of Chemistry, 2016)
The YFe1-xCoxO3 (x = 0.1; 0.2; 0.3) nanomaterials have been synthesized by co-precipitation through the hydrolysis of Y(III), Co(II) and Fe(III) cations in boiling water with the present of KOH 5 % precipitating agent. The results show that when the ratio of Co(II)-doped in YFeO3 crystals increases from 0.1 to 0.3, the size crystal decreases from 31.6 nm to 28.1 nm, the saturation magnetization decreases from 1.718 emu/g to 0.565 emu/g; the coercive force increases from 83.30 to 134.77 Oe and the excess magnetism increases from 47,567×10-3 to 64,764×10-3 emu/g.